The impact of Duolingo in developing students’ linguistic competence: an aspect of communicative language competences (Educação e Pesquisa, 2023)
This paper reports the impact of a type of m-learning on developing students’ linguistic and communicative competence in English as a second language. This study is a Mexican-based case using Duolingo to improve virtual courses in higher education students whose first language is Spanish. This study is a quasi-experimental research that analyzed pre-test and post-test results on a sample of 40 participants (control group of 20 participants and experimental group of 20 participants). The measuring instruments were designed for this specific study and focused on testing the six components of linguistic competence according to CEFR at level A2 (2018). A pilottest was previously conducted, and pre-test (0.81) and post-test (0.98) coefficients were considered acceptable according to Cronbach’s Alpha. This study addressed the following questions: a) How does Duolingo contribute to the development of linguistic competence in higher education students and support English learning in virtual courses via the m-learning methodology? and b) Which components were improved in student´s linguistic competence after using Duolingo? Results revealed a profound improvement in the experimental group participants. The post-test result of the experimental group is superior ( M=43.75) compared with the control group (M=30.35), mainly in the phonological control (+5.20) and the orthographic control (+2.65) compared with the control group, whose score slightly increased primarily attributed to the English virtual classes.